2011
DOI: 10.1111/j.1755-3768.2011.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of colour Doppler imaging in ocular blood flow research

Abstract: . The main objective of this report is to encourage consistent quality of testing and reporting within and between centres that use colour Doppler imaging (CDI) for assessment of retrobulbar blood flow. The intention of this review is to standardize methods in CDI assessment that are used widely, but not to exclude other approaches or additional tests that individual laboratories may choose or continue to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
1
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 156 publications
(279 reference statements)
1
136
1
18
Order By: Relevance
“…Before the study the intra-observer concordance was tested and all the examiners showed an acceptable degree of reproducibility with both devices [12]. Examiners conducted the examination in accordance with the methods reported by previous investigations [7].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the study the intra-observer concordance was tested and all the examiners showed an acceptable degree of reproducibility with both devices [12]. Examiners conducted the examination in accordance with the methods reported by previous investigations [7].…”
Section: Data Collectionmentioning
confidence: 99%
“…Color Doppler imaging (CDI) is a non-invasive technique used to evaluate blood flow of the eye, not affected by poor ocular media, with acceptable intra-observer reproducibility [7] which shows perfusion abnormalities in POAG patients [8,9]. Despite this, it is difficult to establish the causal role of ischemia in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…6,19,[28][29][30] Doppler OCT is a promising approach for measuring retinal blood flow. If absolute blood flow is to be measured, the angle ambiguity of the Doppler techniques has to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler imaging measures blood velocities in retrobulbar vessels, but no information on vessel diameters is available. 6 Laser Doppler flowmetry and speckle flowgraphy can be used to assess choroidal and optic nerve blood flow in relative units. 7,8 For several years, the only technique providing information about retinal blood flow was the combined measurement of retinal blood velocity via laser Doppler velocimetry (LDV) and of vessel diameters using fundus photographs.…”
Section: Introductionmentioning
confidence: 99%
“…К современным методам исследования глазного кровотока относятся [10][11][12][13][14][15][16] цветовое допплеров-ское картирование (ЦДК), сканирующая лазерная допплеровская флоуметрия, определение диаметра ретинальных сосудов и их ветвей на анализаторе со-судов сетчатки, лазерная спекл-флоуграфия, позво-ляющая измерить диаметр, цифровая сканирующая лазерная офтальмоскопическая ангиография, рети-нальная оксиметрия и оптическая когерентная то-мография (ОКТ) с функцией допплера (DOCT). Подробное описание указанных методов приведено нами ранее [17].…”
unclassified